Direct optical observation of walls and disclination effects in active photonic devices - Snow, B.D.; Adikan, Faisal Rafiq Mahamd; Gates, J.C.; Gawith, C.B.E.; Dyadyusha, A.; Major, H.E.; Kaczmarek, M.; Smith, P.G.R. (2009)
Liquid crystal tunable Bragg Gratings defined in planar substrates via a laser patterning technique exhibit complex wavelength tuning. This tuning displays threshold points and hysteresis. These tuning features are shown to be a manifestation of physical processes occurring in the confined geometry of our tunable devices. Such physical processes include the formation and removal of line disclinations and an associated wall. We discuss the effect of walls in the liquid crystal with regards to voltage tuning characteristics and whether they may allow faster wavelength tuning.